2017
DOI: 10.1080/01676830.2017.1383478
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-related orbital disease masquerading as thyroid eye disease, vice versa, or both?

Abstract: A 40 year-old male presented after one year of unilateral, progressive, steroid-responsive, orbital inflammatory disease causing proptosis, extraocular muscle (EOM) restriction, and compressive optic neuropathy. The development of anti-thyroidal antibodies prompted the diagnosis of thyroid eye disease (TED); however, the prolonged active phase, remarkable reversibility of ophthalmic features with high-dose corticosteroids, unilaterally of disease, uncharacteristic EOM involvement (including both obliques), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…This needs to be interpreted with caution as the study analyzed mostly specimens obtained from orbital fat, while only four biopsies were obtained from the lacrimal gland and none from extraorbital muscles [85]. This is confirmed by the case report of a patient with GO, in which no staining for IgG4 in the lacri-mal gland and orbital fat was demonstrated but 24 IgG4(+) cells in HPF and fibrosis in an enlarged extraorbital muscle biopsy [86].…”
Section: Role Of Igg4 In Graves' Disease and Orbitopathymentioning
confidence: 74%
See 1 more Smart Citation
“…This needs to be interpreted with caution as the study analyzed mostly specimens obtained from orbital fat, while only four biopsies were obtained from the lacrimal gland and none from extraorbital muscles [85]. This is confirmed by the case report of a patient with GO, in which no staining for IgG4 in the lacri-mal gland and orbital fat was demonstrated but 24 IgG4(+) cells in HPF and fibrosis in an enlarged extraorbital muscle biopsy [86].…”
Section: Role Of Igg4 In Graves' Disease and Orbitopathymentioning
confidence: 74%
“…There are currently a handful of case reports describing patients with GO, and the biopsy procedure confirmed IgG4(+) plasma cell infiltration of the orbital tissue [86][87][88]. In those cases, biopsies were obtained most often not from the orbital fat but from the extraorbital muscle, lacrimal gland, or infiltrative orbital masses.…”
Section: Role Of Igg4 In Graves' Disease and Orbitopathymentioning
confidence: 99%
“…29 Both IgG4-ROD and TED can have bilateral and multiple EOM enlargement radiologically. 30,31 Komatsu et al 32 reported that up to 27% of autoimmune pancreatitis patients were associated with hypothyroidism, indicative of thyroid involvement in IgG4-RD. Tooley et al 33 suggested that the key features to distinguish IgG4-ROD from TED were disproportionately large lateral rectus muscle and the enlarged infraorbital nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Case reports describing eye diseases masquerading as Graves’ ophthalmopathy can be found in the literature; 5 , 6 however, only a few cases demonstrated idiopathic orbital inflammation and thyroid eye disease occurring concurrently. While clinicians frequently order imaging in these cases, imaging is often inconclusive.…”
Section: Discussionmentioning
confidence: 99%